SNA + MC 2013 - Joint International Conference on Supercomputing in Nuclear Applications + Monte Carlo 2014
DOI: 10.1051/snamc/201404105
|View full text |Cite
|
Sign up to set email alerts
|

Shared Memory Parallelism for 3D Cartesian Discrete Ordinates Solver

Abstract: This paper describes the design and the performance of DOMINO, a 3D Cartesian SN solver that implements two nested levels of parallelism (multicore+SIMD) on shared memory computation nodes. DOMINO is written in C++, a multi-paradigm programming language that enables the use of powerful and generic parallel programming tools such as Intel TBB and Eigen. These two libraries allow us to combine multi-thread parallelism with vector operations in an efficient and yet portable way. As a result, DOMINO can exploit th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…This last change can divide by up to four the arithmetic intensity of the kernel. This confirms the preliminary results on shared memory systems with INTEL TBB presented in [18] against the DENOVO and PENTRAN code.…”
Section: Comparison With Snap/partisnsupporting
confidence: 87%
See 2 more Smart Citations
“…This last change can divide by up to four the arithmetic intensity of the kernel. This confirms the preliminary results on shared memory systems with INTEL TBB presented in [18] against the DENOVO and PENTRAN code.…”
Section: Comparison With Snap/partisnsupporting
confidence: 87%
“…However, given that modern supercomputer architectures are becoming more and more heterogeneous (presence of accelerators inside computing nodes) and hybrid (interconnection of several nodes), it may be important to review classical parallel programming models as shown in the paper [17]. In a previous work [18], we have presented the DOMINO neutron transport solver designed for those modern architectures. We have especially showed that: 1) a good data locality dramatically improves arithmetic intensity of the sweep operation, and allows us to efficiently exploit SIMD units available inside current processors; 2) usage of the task-based programming model helped us to parallelize the sweep of DOMINO, by relying on INTEL TBB [19] library that addresses shared memory supercomputing nodes.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of a shared memory node has also been investigated [17]. Intel Thread Building Block (TBB) tasks were used to maintain a task dependency graph of cells within a wavefront.…”
Section: Related Workmentioning
confidence: 99%
“…The performance of a shared memory node has also been investigated [13]. Intel Thread Building Block (TBB) tasks were used to maintain a task dependency graph of cells within a wavefront.…”
Section: Related Workmentioning
confidence: 99%